Engineering the risk out of uncertain but high potential investments - MacMillan, Ian (Henry Stewart Talks, 2014)
Creative ways for “de-risking” highly uncertain but high potential opportunities, Enhancing a call, Market uncertainty, Conventional NPV vs. Engineered risk thinking, Creating abandonment value and a real put
Reviewed at 2020/07/30